Challenges for municipal solid waste management practices in Vietnam - Nguyen Duc Luong; Hoang Minh Giang; Bui Xuan Thanh; Nguyen The Hung (Diponegoro University, 2013)
Municipal solid waste (MSW) management is currently one of the major environmental problems facing by Vietnam. Improper management of MSW has caused adverse impacts on the environment, community health, and social-economic development. This study attempts to provide a review of the generation and characterization, disposal and treatment technologies of MSW to evaluate the current status and identify the problems of MSW management practices in Vietnam. Finally, this study is concluded with fruitful recommendations which may be useful in encouraging the responsible agencies to work towards the further improvement of the existing MSW management system.Doi: http://dx.doi.org/10.12777/wastech.1.1.17-21Citation: Luong, N.D., Giang, H.M., Thanh, B.X. and Hung, N.T. 2013. Challenges for municipal solid waste management practices in Vietnam. Waste Technology 1(1):6-9.Doi: http://dx.doi.org/10.12777/wastech.1.1.17-21